Uma análise dos dados da violência doméstica no estado do Tocantins a partir do sistema E-proc - Marques, Fabiano Gonçalves (Universidade Federal do Tocantins, 2017)
The objective of this Technical Report is to present the data of violence effectively judicialized in the Domestic Violence Sticks of the state of Tocantins, based on information obtained in the system of digital process of the Court of Justice (TJ), entitled Electronic System of Processes (E-PROC ). It was considered as a problem that the system provided only the raw data, but without distinguishing the criminal types. In addition, it was found that accessibility to information is available only to the servants and magistrates of the judiciary. From the request and capture of data stored in the period between 2013 and 2015, in the fortytwo Counties existing in the state, it was possible to develop a specific methodology for analysis and cataloging of different types of crime, considering the levels of violence, separating them by Group and according to similarity. This procedure allowed the construction of detailed tables and graphs according to the levels of violence practiced by city, as follows: high, rising, stable, decreasing and low. The product presented is an access link, housed on the state's TJ website, containing detailed information on domestic violence numbers. All content - tables and graphs - can be accessed on a virtual geographic map that, with a simple click, leads any researcher or visitor directly to the data of violence, duly specified and individualized, by region and city. The map can be updated monthly by TJ's servers. It is understood that the access to these data by the adjacent population and the researchers of the subject can help in the construction of public policies in the places where the indices are high or in increasing process, besides possible advances in researches that can help in the minimization of the Problem of domestic violence where it is necessary.